1028. Synergizing Infectious Diseases and Substance Use Treatment to Improve the Outcomes of Endocarditis in People Who Inject Drugs at a Large Academic Hospital. (26th November 2018) - Meisner, Jessica; Koenig, Helen; Tebas, Pablo
Abstract: Background: Philadelphia is at the epicenter of the urban opioid epidemic: currently more than 70, 000 individuals use heroin and in the year 2017 there were 1, 200 overdose deaths. Endocarditis in patients with opioid use disorder (OUD) requires long hospitalizations for IV antibiotic use that delays the initiation of rehabilitation and opioid replacement therapy. We decided to implement an integrative approach to both problems. During the first step (this study), we evaluated the current care and identified areas that could be improved and in a second step developed an intervention with the goal to improve long-term outcomes. Methods: We conducted a retrospective chart review of patients admitted to the Hospital of University of Pennsylvania with infective endocarditis (IE) and OUD from July 2016 to June 2017. Patients were identified via ICD-10 codes for infective endocarditis and substance use. Results: Among the 669 admissions for patients with a diagnosis of OUD, 37 had IE (33 unique patients). Seventy-three percent of those required valve replacement surgery. Mean length of stay was 32 days (IQR 16, 49), 10% left against medical advice. The overall readmission rate was 55%. The most common valves involved were tricuspid with 20 (54%) and 10 aortic (27%). On discharge, only 6 (18%) of the patients were discharged on Medication Assisted Treatment (MAT), 14 (38%) were discharged with prescriptions for narcotics, and zero for naloxone. HIV testing was not performed on 7 (21%) patients and 1 patient was HIV positive. Twenty-three (70%) patients were antibody positive for HCV, seven (21%) were antibody negative, three (9%) were not tested. S. aureus was the causal pathogen in 25 (76%) cases, with seven (19%) being methicillin resistant. Conclusion: The lack of a systematic approach to management of patients with OUD admitted for endocarditis represents a missed opportunity to improve the care and outcomes of patients with OUD in regards to withdrawal, relapse prevention and harm reduction. We designed, implemented, and started to evauate an intervention to initiate MAT in conjuction with the managament of the infectious diseases complications and a standardized approach to screening these patients for HIV, hepatitis B/C and offering PrEP, HIV therapy, and/or HCV therapy where appropriate. Disclosures: All authors: No reported disclosures.